Tinjauan Yuridis dalam Pasar Modal: Analisis Tahapan Initial Public Offering (Ipo) - Hilda Amadea Sobandi; Muhammad Farel Andaresta; Reynara Shafira Putri Indrayana (Jurnal Syntax Admiration, 2024)
In today's competitive business era, entrepreneurs are faced with the challenge of growing their businesses in an increasingly competitive environment. One of the main strategies for growth is business expansion, which often requires additional funding. Internal funding is often insufficient, so many companies turn to external sources of funds, such as through an Initial Public Offering (IPO). IPOs are defined in Law No. 8/1995 on Capital Markets and offer various benefits, including increased share ownership by individual investors, expansion of product distribution, and long-term investor support. However, some listed companies choose not to list their shares on the Indonesia Stock Exchange, a decision that complies with the Capital Market Law. A company can be classified as a public company if it meets certain criteria, including the number of shareholders and minimum paid-up capital. While not listing on the stock exchange may have its own benefits and drawbacks, this decision has significant implications for the company's operations. This study explains the dynamics and implications of various funding strategies in the current business context, providing insights into the IPO decision and the choice not to list on the stock exchange.